Applications of Operational Research and Mathematical Models in Management - Chalikias, Miltiadis (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
One of the most significant of the many challenges we face is how to sustain the production of food for a growing population without compromising the health of our planet. This book addresses the growing challenges of the interrelated issues of food security, social stability, and the increasing scarcity of the planet's resources to propose sophisticated modeling innovations leading to practical approaches and solutions to multiple facets of these challenges.